2017
DOI: 10.1016/j.jid.2017.04.034
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1 Inhibition Regulates UVB-Induced Skin Inflammation and Tumorigenesis in Xpa-Deficient Mice

Abstract: Xeroderma pigmentosum complementation group A is a hereditary disease characterized by early onset of skin cancers and freckle-like pigmented maculae in sun-exposed sites. Although the etiology of the predisposition to UVR-induced skin tumors in xeroderma pigmentosum complementation group A is well investigated as a repair deficiency in UVR-induced DNA damage, the mechanism of exaggerated sunburn in patients with xeroderma pigmentosum complementation group A and whether UVR-induced inflammation relates to a sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…Mouse embryonic fibroblasts (MEFs) were prepared from E13.5 embryos of Xpa ‐knockout and wild‐type mice . The MEFs of each Xpa genotype were exposed to 0.20 kJ m −2 broadband UVB following the addition of 10 μg mL −1 voriconazole, 10 μg mL −1 voriconazole N‐oxide (VN‐oxide), or 10 ng mL −1 HCTZ in PBS and incubation until the time point of corresponding DNA isolation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mouse embryonic fibroblasts (MEFs) were prepared from E13.5 embryos of Xpa ‐knockout and wild‐type mice . The MEFs of each Xpa genotype were exposed to 0.20 kJ m −2 broadband UVB following the addition of 10 μg mL −1 voriconazole, 10 μg mL −1 voriconazole N‐oxide (VN‐oxide), or 10 ng mL −1 HCTZ in PBS and incubation until the time point of corresponding DNA isolation.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, nonmelanoma skin cancer and melanoma may develop in the sun‐exposed area of the skin after a long‐term voriconazole administration , featuring multiple squamous cell carcinomas and their precursor lesions, actinic keratosis, distributed over the face and neck . We previously showed that UVB‐induced inflammatory response was highly associated with DNA damage caused by UVB, such as 8‐oxo‐7,8‐dihydroguanine (8‐oxoGua) and cyclobutane pyrimidine dimers (CPDs) using Ogg1 knock‐out mice or Xpa ‐knockout mice, which are deficient in repairing DNA damage, 8‐oxoGua or CPDs, respectively Namely, Ogg1 ‐knockout mice and Xpa ‐knockout mice produced more intense UV‐induced inflammatory response and expressed much higher inflammatory cytokines such as CXCL1 . The study has also shown that Ogg1 ‐knockout mice and Xpa ‐knockout mice are more susceptible to UV‐induced tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin specimens were fixed in 10% neutralized formalin and embedded in paraffin. Immunohistochemical staining for CPD detection was performed using a monoclonal antibody against CPD (TDM‐2 1:5,000 dilution) as described previously ( 22 ). Specimens were observed using a Biozero BZ‐X710 microscope (Keyence, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The NLRP3 inflammasome protein complex, related to IL-1α and NF-κB, has also been shown to be activated by UV-induced DNA damage (124). These proinflammatory pathways have been proposed to be a type of UV-induced DNA damage response, with NER having a major role in regulating the pathways involved in this process (222). Moreover, UV induced inflammation has also been shown to have a role in tumorigenesis alongside UV photolesions themselves (223), with the inhibition of inflammation resulting in a decrease in cancer incidence after chronic UV irradiation in both NER proficient and deficient mice (224,225).…”
Section: Senescence and Inflammationmentioning
confidence: 99%